HYPNOANXIETY AS AN ALTERNATIVE THERAPY TO REDUCE ANXIETY IN PRIMIGRAVIDA MOTHERS - Nurul Jannah; Hadi Hadi; Sri Rahayu; Soeharyo Hadisaputro; Diyah Fatmasari; Imam Djamaluddin Mashoedi (Belitung Nursing Journal, 2017)
Background: Anxiety among primigravida mothers should be handled to avoid the risks during pregnancy. Hypnotherapy is considered to be a solution; however, there are limited studies to determine its effect on anxiety, especially in primipara mothers. Objective: To examine the effect of hypnoanxiety on the level of anxiety in primigravida. Methods: This was a Randomized Controlled Trials (RCTs) with pretest-posttest design, conducted between September – October 2016 in the working area of the Health Center of Bergas Semarang, Indonesia. There were 40 respondents recruited using simple random sampling, which divided into intervention and control group. Hypnoanxiety was performed 8 times for 4 weeks. The Zung Self-Rating Anxiety Scale (ZSAS) was used to measure anxiety in pregnant women. Data were analyzed using Mann Whitney test and Kruskal Wallis test. Results: Findings showed that after four weeks intervention, there was a decrease of the level of anxiety in the intervention group, consisted of 25% of moderate anxiety, 40% of mild anxiety, and 35 % of respondents with no anxiety. The p-value was 0.05, which indicated that there was mean difference of anxiety level between intervention and control group. Conclusions: There was a significant effect of hypnoanxiety on the level of anxiety in pregnant women. It is suggested that hypnoanxiety could be one of the alternative therapies to reduce the anxiety among pregnant women. This could be considered to be included in the standard of midwifery care in Indonesia.